Changes in nutritional metabolites of young ginger (Zingiber officinale Roscoe) in response to elevated carbon dioxide - Ghasemzadeh, Ali; Jaafar, Hawa Z. E.; Karimi, Ehsan; Ashkani, Sadegh (MDPI, 2014)
The increase of atmospheric CO2 due to global climate change or horticultural practices has direct and indirect effects on food crop quality. One question that needs to be asked, is whether CO2 enrichment affects the nutritional quality of Malaysian young ginger plants. Responses of total carbohydrate, fructose, glucose, sucrose, protein, soluble amino acids and antinutrients to either ambient (400 μmol/mol) and elevated (800 μmol/mol) CO2 treatments were determined in the leaf and rhizome of two ginger varieties namely Halia Bentong and Halia Bara. Increasing of CO2 level from ambient to elevated resulted in increased content of total carbohydrate, sucrose, glucose, and fructose in the leaf and rhizome of ginger varieties. Sucrose was the major sugar followed by glucose and fructose in the leaf and rhizome extract of both varieties. Elevated CO2 resulted in a reduction of total protein content in the leaf (H. Bentong: 38.0%; H. Bara: 35.4%) and rhizome (H. Bentong: 29.0%; H. Bara: 46.2%). In addition, under CO2 enrichment, the concentration of amino acids increased by approximately 14.5% and 98.9% in H. Bentong and 12.0% and 110.3% in H. Bara leaf and rhizome, respectively. The antinutrient contents (cyanide and tannin) except phytic acid were influenced significantly (P ≤ 0.05) by CO2 concentration. Leaf extract of H. Bara exposed to elevated CO2 exhibited highest content of cyanide (336.1 mg HCN/kg DW), while, highest content of tannin (27.5 g/kg DW) and phytic acid (54.1 g/kg DW) were recorded from H.Bara rhizome grown under elevated CO2. These results demonstrate that the CO2 enrichment technique could improve content of some amino acids and antinutrients of ginger as a food crop by enhancing its nutritional and health-promoting properties.